DIGITALISASI KEUANGAN SYARIAH MENUJU KEUANGAN INKLUSIF: KERANGKA MAQASHID SYARIAH - Nurfalah, Irfan; Rusydiana, Aam Slamet (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 2019)
Sharia financial literacy and financial inclusion in indonesia are still in the lower level, Indonesian’s Financial Services Authority launched in 2016 that the data of sharia financial literacy is about 8.11% and sharia financial inclusion only about 11.06%. The easiness of access against sharia financial products and services are the main factors that caused both are still in the lower level. In case of enhancement of society knowledge and access needs the innovation to simplify the utilization of sharia financial products and services. One of the best innovation must be developed by Sharia Financial Institution is digitalization.The digitalization will affect the increase of sharia financial literacy and inclusion index, because this era is an open public information, most people now are easy to access the internet and also the smartphone users in Indonesia are increasing every year. So this is an opportunity for Sharia Financial Institution to combine their products and services with the latest technology. The author makes a digital innovation solution to accommodate these opportunities, named "Connected, One Stop Solution" which are 20 features that can be enjoyed by all segments of society. In addition, the 20 features are adapted to sharia rules which refer to maqashid sharia.